Zero Fraud Plan - Safiih, Abdul Rahman; Tahalea, Bagas Zadrak (IJESS International Journal of Education and Social Science, 2025)
This study analyzes the implementation of the Zero Fraud Program in reducing fraud rates and its impact on employee performance at PT Usaha Garda Arta, Depok Branch. This study uses a qualitative approach with interview methods, observation, and document analysis of five key informants. SWOT analysis is used to evaluate the strengths, weaknesses, opportunities and threats of this program. The results of the study indicate that the Zero Fraud Program is effective in reducing fraud rates through strict supervision, anti-fraud fires, and ongoing training. However, there are still obstacles such as limited technology, minimal management involvement, and employee resistance to change. Although this program is able to reduce fraud cases, problems such as high absenteeism, low work motivation, and lack of employee understanding of anti-fraud policies are still obstacles to improving performance. This program has a positive impact on productivity, time efficiency, and work quality, but it needs improvement in technology integration, increasing policy transparency, and communication between management and employees. This study recommends the implementation of a more comprehensive fraud prevention framework, increasing management participation, and performance-based incentive training, and developing an integrity-based work culture will increase the effectiveness of fraud prevention in the long term.